Medieval London Widows, 1300-1500. - Barron, Caroline (Continuum International Pub. Group, 1994)
"Medieval London Widows, 1300-1500 shows that it is possible to expand the repertoire of examples of medieval women with personalities and individuality beyond the well-known triad of Margaret Paston, Margery Kempe and the Wife of Bath. The rich documentation of London records allows these women to speak for themselves. They do so largely through their wills, which themselves exemplify the ability of widows to make choices and to order their lives."--Bloomsbury Publishing.